Development of Anthropomorphic Robot Finger for Violin Fingering. Issue 6 (1st December 2016) - Park, Hyeonjun; Lee, Bumjoo; Kim, Donghan
Abstract : This paper proposes a robot hand for a violin‐playing robot and introduces a newly developed robot finger. The proposed robot hand acts as the left hand of the violin‐playing robot system. The violin fingering plays an important role in determining the tone or sound when the violin is being played. Among the diverse types of violin fingering playing, it is not possible to produce vibrato with simple position control. Therefore, we newly designed a three‐axis load cell for force control, which is mounted at the end of the robot finger. Noise is calculated through an analysis of the resistance difference across the strain gauge attached to the proposed three‐axis load cell. In order to ensure the stability of the three‐axis load cell by analyzing the stress distribution, the strain generated in the load cell is also verified through a finite element analysis. A sound rating quality system previously developed by the authors is used to compare and analyze the sound quality of the fourth‐octave C‐note played by a human violinist and the proposed robot finger.